2015
DOI: 10.1002/2015gl063926
|View full text |Cite
|
Sign up to set email alerts
|

Response of sea surface fugacity of CO2 to the SAM shift south of Tasmania: Regional differences

Abstract: Using observational data collected south of Tasmania during 14 austral summer cruises during 1993–2011, we examined the response of sea surface fugacity of carbon dioxide (fCO2) to the Southern Annular Mode (SAM) shift, which occurred around 2000. In the southern part of the Southern Ocean (SO) or the Polar Zone (PZ) and the Polar Frontal Zone (PFZ), fCO2 increased faster at the sea surface than in the atmosphere before the SAM shift, but not after the shift. In the northern part of the SO or the Subantarctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
8
20
1
Order By: Relevance
“…This concurs with previous studies, which suggested that the increase in the SAM during the 1990s resulted in the weakening of the Southern Ocean sink (Le Quéré et al, 2007;Lenton and Matear, 2007;Lovenduski et al, 2007;Lenton et al, 2009;Xue et al, 2015). The work by Fogt et al (2012) bridges the gap between the proposed asymmetric atmospheric circulation of Landschützer et al (2015) and the observed correlation with the SAM of Landschützer et al (2016).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This concurs with previous studies, which suggested that the increase in the SAM during the 1990s resulted in the weakening of the Southern Ocean sink (Le Quéré et al, 2007;Lenton and Matear, 2007;Lovenduski et al, 2007;Lenton et al, 2009;Xue et al, 2015). The work by Fogt et al (2012) bridges the gap between the proposed asymmetric atmospheric circulation of Landschützer et al (2015) and the observed correlation with the SAM of Landschützer et al (2016).…”
Section: Introductionsupporting
confidence: 92%
“…Conversely, in the eastern Pacific sector of the Southern Ocean, strong cooling overwhelmed increased upwelling . This is supported by observations from the Drake Passage and south of Australia showing that variability of upwelling has affected pCO 2 (Munro et al, 2015;Xue et al, 2015).…”
Section: Introductionsupporting
confidence: 68%
“…Nevertheless, these studies tended to support a weakening sink trend up to the mid 2000s. One of these studies (9) also pointed out that the trend may have reversed in recent years, a finding corroborated by the analysis of pCO 2 observations along a single meridional transect south of Tasmania (11).…”
mentioning
confidence: 73%
“…followed by a substantial strengthening of the Southern Ocean CO 2 sink since 2002 [Fay and McKinley, 2013;Landschützer et al 2015a;Munro et al 2015a;Xue et al 2015]. Continued observational sampling efforts and coordination are required for quantifying and understanding decadal changes in this important CO 2 sink region.…”
Section: !mentioning
confidence: 99%